K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

16 tháng 7 2021

(x - 4)2 = (x - 4)4

Ta có: 12 = 14 ; 02 = 04

\(\Rightarrow\orbr{\begin{cases}x-4=1\\x-4=0\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=5\\x=4\end{cases}}\)

24 tháng 10 2019

x3 + x + 2

\(=x^3+x^2-x^2-x+2x+2\)

\(=x^2\left(x+1\right)-x\left(x+1\right)+2\left(x+1\right)\)

\(\left(x+1\right)\left(x^2-x+2\right)\)

c) x3 + 32x - 4

\(=x^3-x^2+4x^2-4x+4x-4\)

\(=x^2\left(x-1\right)+4x\left(x-1\right)+4\left(x-1\right)\)

\(=\left(x-1\right)\left(x^2+4x+4\right)\)

\(=\left(x-1\right)\left(x+2^2\right)\)

d)x3y3 + x2y2 + 4

\(=x^3y^3-4xy+x^2y^2-4xy+4\)

\(=xy\left(x^2y^2-4\right)+\left(xy+2\right)^2\)

\(=xy\left(xy-2\right)\left(xy+2\right)+\left(xy+2\right)^2\)

\(=\left(xy+2\right)\left(xy\left(xy-2\right)+xy+2\right)\)

\(=\left(xy+2\right)\left(x^2y^2-2xy+xy+2\right)\)

\(=\left(xy+2\right)\left(x^2y^2-xy+2\right)\)  

e) x3 + 3x2y - 9xy2 + 5y3

\(=x^3-3x^2y+3xy^2-y^3+6x^2y-12xy^2+6y^3\)

\(=\left(x-y\right)^3\left(x^2-2xy+y^2\right)\)

\(=\left(x-y\right)^3\left(x-y\right)^2=\left(x-y\right)^2\left(x-y-1\right)\)

8 tháng 4 2018

a) M(x) + N(x) + P(x) = x5 + 7x4 - 6x3 - 3x2 + x - 4

30 tháng 5 2018

a)\(F\left(x\right)=2\left(x^4+x^3\right)+2x-4\left(x^2-x^3-1\right)+4\)

\(=2x^4+2x^3+2x-4x^2+4x^3+4+4\)

\(=2x^4+6x^3+2x-4x^2+2x+8\)

\(G\left(x\right)=5x^4-4\left(3+x^4\right)-2x^2+4x^3+2\left(x^3-x^2+x\right)\)

\(=5x^4-12-4x^4-2x^2+4x^3+2x^3-2x^2+2x\)

\(=x^4+6x^3-4x^2+2x-12\)

30 tháng 5 2018

b) Tìm \(K\left(x\right)=F\left(x\right)+G\left(x\right)\)

\(\dfrac{+\dfrac{F\left(x\right)=2x^4+6x^3-4x^2+2x+8}{G\left(x\right)=x^4+6x^3-4x^2+2x-12}}{K\left(x\right)=3x^4+12x^3-8x^2+4x-4}\)

Tìm \(H\left(x\right)=F\left(x\right)-G\left(x\right)\)

\(\dfrac{-\dfrac{F\left(x\right)=2x^4+6x^3-4x^2+2x+8}{G\left(x\right)=x^4+6x^3-4x^2+2x-12}}{H\left(x\right)=x^4+0-0+0+20}\)

19 tháng 6 2020

(2x+2x-4)-(-x+x- 2x2 -4)

=2x2+2x-4+x-x3+2x2+4

=(2x2+2x2)+(2x+x)+(-4+4)-x3

=4x2+3x-x3

(-x+ x- 2x-4) - (2x- 2x -4)

=-x+x3-2x2-4-2x2+2x+4

=(-x+2x)+(-2x2-2x2)+(-4+4)+x3

=x-4x2+x3

Ta có : \(\left(2x^2+2x-4\right)-\left(-x+x^3-2x^2-4\right)\)

\(=2x^2+2x-4+x-x^3+2x^2+4=4x^2+3x\)

\(\left(-x+x^3-2x^2-4\right)-\left(2x^2-2x-4\right)\)

\(=-x+x^3-2x^2-4-2x^2+2x+4=x+x^3-4x^2\)

5 tháng 8 2018

A = \(4\left(x-5\right)-x^2\left(x+1\right)-x^3\left(x-3\right)-\left(x-4+x^2\right)\)

A = \(4x-20-x^3-x^2-x^4+3x^3-x+4-x^2\)

A = \(-x^3-3x^3-x^2+x^2-x^4+4x-x-20+4\)

A = \(-4x^3-x^4+4x-16\)

B = \(-3\left(x^2-x+1\right)-2\left(4-x^2\right)-6\left(x+1\right)-x^4-x^3\)

B = \(-3x^2+3x-3-8+2x^2-6x-6-x^4-x^3\)

B = \(-x^4-x^3-3x^2-2x^2+3x-6x-3-8-6\)

B = \(-x^4-x^3-5x^2-3x-17\)

C = \(-\left(x^4+3x^2-2\right)-x^2\left(5-x\right)+3\left(x-1\right)\)

C = \(-x^4-3x^2+2-5x^2+x^3+3x-3\)

C = \(-x^4+x^3-3x^2+5x^2+3x+2-3\)

C = \(-x^4+x^3-2x^2+3x-1\)

#Yiin

5 tháng 8 2018

\(A=4x-20-x^3-x-x^4+3x^3-x+4-x^2\)

\(=-x^4+2x^3-x^2+2x-16\)

\(B=-3x^2+3x-3-8+2x^2-6x-6-x^4-x^3\)

\(=-x^4-x^3-x^2-3x-17\)

\(C=-x^4-3x^2+2-5x^2+x^3+3x-3\)

\(=-x^4+x^3-8x^2+3x-1\)

Từ đó có:

\(A-B=-x^4+2x^3-x^2+2x-16-\left(-x^4-x^3-x^2-3x-17\right)\)

\(=-x^4+2x^3-x^2+2x-16+x^4+x^3+x^2+3x+17\)\(=3x^3+5x+1\)

\(B-C=-x^4-x^3-x^2-3x-17-\left(-x^4+x^3-8x^2+3x-1\right)\)

\(=-x^4-x^3-x^2-3x-17+x^4-x^3+8x^2-3x+1\)

\(=-2x^3+7x^2-6x-16\)

\(C-A=-x^4+x^3-8x^2+3x-1-\left(-x^4+2x^3-x^2-2x-16\right)\)

\(=-x^4+x^3-8x^2+3x-1+x^4-2x^3+x^2+2x+16\)

\(=-x^3-7x^2+5x+15\)

14 tháng 5 2020

a) M + x2 - 3x + 4 = - (7x3 - 5x2 + x - 5)

⇒M=- (7x3 - 5x2 + x - 5) - (x2 - 3x + 4)

⇒M=-(7x3 - 5x2 + x - 5 + x2 - 3x + 4)

⇒M=-(7x3 - 4x2 - 2x - 1)

b) 5 (x2 - 3) + x4 + N = x3 - 4 ( x2 -1)

⇒N = x3 - 4 ( x2 -1) - 5 (x2 - 3) + x4

⇒N = x3 - 4x2 +4 - 5x2 + 15 + x4

⇒N = x4 + x3 - 9x2 +19